INVENTION OF A NEW INDEX FOR THE DETERMINATION OF SEXUAL MATURITY IN FISHES - DOBRIYAL, ANOOP K.; RAUTELA, KUM KUM; RAUTELA, A. S. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1999)
The paper deals with the interpretation and importance of a newly invented index for the determination of sexual maturity, month and frequency of spawning in fishes. The index is named as Dobriyal Index (D.I.).